Effect of climate change on potential distribution of oriental beech (Fagus orientalis Lipsky.) in the twenty-first century in Turkey - AYAN, Sezgin; BUGDAY, Ender; VAROL, Tugrul; ÖZEL, Halil Barış; THURM, Eric Andreas (Springer Science and Business Media LLC, 2022)
The rising temperatures and decreasing rainfall are expected to have negative effects on ecosystem services by causing significant shrinkage or shift of forest distribution particularly in Mediterranean basin. In this study, it was aimed to determine the distribution of oriental beech (Fagus orientalis Lipsky.) by modelling the current and future potential locations of the habitats. With Maximum Entropy (MaxEnt) approach, we predicted its distribution under current and future conditions (RCP 4.5 and RCP 8.5) in Turkey. Modelling was performed by using eight bioclimatic variables that show significant relationship to the current distribution of oriental beech and were widely used in the literature. The fitted model had high quality (93.5% AUC) and is biological meaningful. The prediction of warmer condition in future showed that the populations on the southern slopes of the North Anatolian Mountains were expected to shrink and that there would be reduction in the populations found in the main distribution area in the Istranca Mountains and the Northern Anatolia, especially in populations in the transition zone of Central Anatolia. Also, oriental beech would lose its isolated-marginal populations in the southeast of Turkey. The results highlight the importance of a genetic conservation programme for beech population in Turkey. Otherwise, the genetic pools seem to extinct under climate change. Furthermore, the paper is intended to provide a starting point for a monitoring of oriental beech at the edge of its distribution, to observe its climatic migration.
Keywords: Atmospheric Science; Western Black-Sea; Tree Species Composition; Temperature; Shift; Precipitation; Growth; Forests; Mountains; Reconstruction; Variability